2016
DOI: 10.1063/1.4971287
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of copper from Cu(i) and Cu(ii) precursors onto HOPG surface: Role of surface defects and choice of a precursor

Abstract: The surface reactivity of two copper-containing precursors, (Cu(hfac) 2 and Cu(hfac)VTMS, where hfac is hexafluoroacetyloacetonate and VTMS is vinyltrimethylsilane), was investigated by dosing the precursors onto a surface of highly ordered pyrolytic graphite (HOPG) at room temperature. The behavior of these precursors on a pristine HOPG was compared to that on a surface activated by ion sputtering and subsequent oxidation to induce controlled surface defects. X-ray photoelectron spectroscopy and energy disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Minimal conversion was seen on the basal planes of highly ordered pyrolytic graphite (HOPG). 96 Our TPD, XPS, and reflection− absorption infrared spectroscopy (RAIRS) studies with 4 on silicon oxide and aluminum oxide flat surfaces (thin films) have indicated measurable thermal activation and decomposition, more extensive on the latter substrate. Figure 5 provides RAIRS data for the adsorbed species obtained after dosing the precursor at different temperatures, and Table 1 lists the peak assignment (based on published analysis for analogous complexes).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimal conversion was seen on the basal planes of highly ordered pyrolytic graphite (HOPG). 96 Our TPD, XPS, and reflection− absorption infrared spectroscopy (RAIRS) studies with 4 on silicon oxide and aluminum oxide flat surfaces (thin films) have indicated measurable thermal activation and decomposition, more extensive on the latter substrate. Figure 5 provides RAIRS data for the adsorbed species obtained after dosing the precursor at different temperatures, and Table 1 lists the peak assignment (based on published analysis for analogous complexes).…”
Section: Resultsmentioning
confidence: 99%
“…However, in later work on ZnO, it was established (again, by IR and DFT) that dissociative adsorption is possible, via the initial removal of the TMVS ligand and the direct coordination of the Cu center to surface OH groups (as expected). , This is followed by the transfer of H surface atoms to the hfac ligand to form Hhfac, leaving the Cu atoms on the surface, and by Cu sintering to form metallic nanoparticles. Minimal conversion was seen on the basal planes of highly ordered pyrolytic graphite (HOPG) . Our TPD, XPS, and reflection–absorption infrared spectroscopy (RAIRS) studies with 4 on silicon oxide and aluminum oxide flat surfaces (thin films) have indicated measurable thermal activation and decomposition, more extensive on the latter substrate.…”
Section: Resultsmentioning
confidence: 99%
“…CasaXPS (version 2.3.16) software was utilized to analyze all the raw data [23]. The carbon peak at 284.6 eV [2426] was used to calibrate the XPS scale.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…Thermal decomposition of the ligands is in fact possible with the latter precursor as well: in experiments with Ru­(TMHD) 3 on a nickel surface, for instance, fractioning of the ligand was seen to yield ketene and 2,2-dimethyl-3-oxopentanal, among other products . It should be noted that in both cases, with Cu­(acac) 2 and Ru­(TMHD) 3 , deposition was studied on metal substrates, which tend to be quite active toward the breaking up of organic adsorbates; other materials such as semiconductors, graphene, or oxides are typically milder and promote less decomposition. , In any case, in more general terms, little is known about the intrinsic effectiveness of the strategy of using bulkier ancillary moieties in β-diketonate ligands to optimize ALD performance in terms of both the related changes in the temperature window where ALD is operational and the extent to which side reactions occur and undesirable impurities are deposited.…”
Section: Introductionmentioning
confidence: 99%